Pengaruh Pembelajaran Model Problem Based Learning Dipadu Team Assisted Individualization terhadap Keterampilan Metakognitif - Din Hadi Shofyan; Aloysius Duran Corebima; Fatchur Rohman (Graduate School of Universitas Negeri Malang, 2020)
Abstract: This study aims to reveal the effect of the PBL model combined with TAI on metacognitive skills. This quasi-experimental research uses a Pretest-Posttest Nonequivalent Control Group Design. Data collection techniques through pretest and posttest. Data were analyzed with the help of SPSS 23 for Windows to determine the effect of the PBL model combined with TAI on metacognitive skills. The results showed that the students' metacognitive skills learned through the PBL model combined with the TAI were significantly higher than through the PBL, TAI and conventional models. The average difference in the PBL model combined with TAI to PBL was 7.38%, PBL combined TAI to TAI was 28.42%, and PBL was combined with TAI to conventional by 29.93%.Abstrak: Tujuan penelitian ini untuk mengungkap pengaruh PBL dipadu TAI terhadap kemampuan metakognitif. Penelitian jenis kuasi eksperimen ini menggunakan rancangan Pretes-Posttest Nonequivalent Control Group Design. Data didapatkan dari nilai pretes dan postes. Analisis data menggunakan uji ANAKOVA dan LSD. Hasil penelitian menunjukkan, keterampilan metakognitif peserta didik melalui pembelajaran PBL dipadu TAI secara signifikan lebih tinggi dibanding melalui model PBL, TAI dan konvensional. Rerata selisih beda model PBL dipadu TAI terhadap PBL sebesar 7,38%, PBL dipadu TAI terhadap TAI sebesar 28,42%, dan PBL dipadu TAI terhadap konvensional sebesar 29,93%.